Advanced strategies for enhancing kaolin ceramics using nanostructured additives: A comprehensive study. - Nasser A M Barakat; Neama A M Eltohamy; Kasem R M Abdelrazek; Wesam Elhawam; Ahmed A A Ammar; Hassan Fouad; Mohamed Hashem; Hak Yong Kim (PLoS ONE)
In this study, we investigated the enhancement of Egyptian kaolin ceramics using various nanostructured additives: polyvinyl alcohol (PVA), titanium dioxide (TiO2) nanofibers, carbon nanotubes (CNTs), silicon dioxide (SiO2) nanoparticles, and activated carbon (AC). The results showed that PVA and TiO2 nanofibers significantly increased the compression strength of the ceramics, with TiO2 nanofibers providing the highest improvement at 2.47 MPa. SEM analysis revealed that these additives facilitated better particle agglomeration, leading to improved mechanical properties. TGA indicated a shift in the sintering reaction peak from 511°C for pristine kaolin to 548°C for PVA-modified kaolin and slightly higher for TiO2-modified kaolin, suggesting enhanced sintering processes. Additionally, the thermal cycling tests demonstrated that TiO2 nanofibers-modified kaolin exhibited exceptional stability, with no change in apparent density, highlighting its potential for refractory applications. PVA-modified samples also showed a significant decrease in porosity and water absorption. These findings underscore the potential of specific nanostructured additives to enhance the mechanical and thermal properties of kaolin ceramics, offering valuable insights for future research and industrial applications.